An approach for identifying in silico peptides against authentic metabolites: in vitro characterization of thymosin beta 4 metabolites - 라하만; Muresan, Anca Raluca; Min, Hophil; Son, Junghyun; Kang, Min-Jung; Kwon, Oh-Seung (한국약제학회, 2022)
Purpose Thymosin beta 4 is a highly active protein that exerts multiple biological activities such as tissue repair, anti-inflammation, and cell maturation. Thymosin beta 4 has also been listed as a prohibited drug by the World Anti-doping Agency (WADA). Based on its biological activities, thymosin beta 4 has a high potential of abuse for the performance enhancement among athletes. This study aimed to investigate and characterize the metabolism of thymosin beta 4 in vitro system. Methods TB4 protein was metabolized in six different enzyme-buffer systems in vitro. After TB4 was metabolized with an appropriate buffer system, the resulting metabolites were detected by high resolution LC-MS/MS. The mass spectrum data of the observed metabolites were characterized in silico, and confirmed the structures based on synthesized authentic standards. Results Total 13 new metabolites, some of which were detected in more than one enzyme system, were found. This study characterized all of the detected metabolites according to their in silico m/z ions and compared our findings with synthesized standards. Finally, metabolites M1, M5, M7, M11, M12, and M13 were confirmed based on their synthesized authentic standards. Conclusion By using an approach for metabolizing a protein to detect, characterize and identify new peptide metabolites, 6 metabolites are identified among 13 expected potential metabolites. Newly detected metabolites may have the potential for biological activities after further screening compared to their parent protein.